The advertisement and aggressive calls of Rhinella abei (Baldissera, Caramaschi, and Haddad, 2004) (Anura: Bufonidae) from Campo Largo, Paraná, Brazil - Batista, Vinicius Guerra; Ramalho, Werther Pereira; Amaral, Diogo Ferreira Do; Maciel, Natan Medeiros; Bastos, Rogério Pereira (Zootaxa, 2016)
Rhinella abei is a medium-sized species (snout-to-vent length 57.0–76.4 mm in males; 60.4–83.9 mm in females—Baldissera et al. 2004) of the Rhinella crucifer species group, distributed in the Brazilian Atlantic Rainforest, from the State of Paraná to northern Rio Grande do Sul (Frost 2016). It is recorded in forested areas (Conte & Rossa-Feres 2007), or while breeding along forest edges and open habitats. Information on advertisement calls of species in the R. crucifer group is available for R. casconi, R. crucifer, R. inopina and R. ornata (Andrade et al. 2015; Heyer et al. 1990; Oliveira et al. 2014; Roberto et al. 2014). Here we describe the advertisement and aggressive calls of R. abei recorded in the municipality of Campo Largo (25.507472° S, 49.376632° W, datum "WGS84"), southeast State of Paraná, Brazil.